Mechanical performance of buried pipe under traffic load-internal pressure coupling action: Experimental and numerical study - Changxi Shan; Wenhao Li (PLoS ONE, 2025)
With the accelerated progress of urbanization, there is an increasing occurrence of buried flexible water distribution pipelines subjected to high internal pressure and heavy loads. The probability of damage to these pipelines is magnified due to traffic load-internal pressure coupling action. Hence, investigating the mechanical performance of buried pipelines under such conditions is a topic of significant research importance. The pipe made of acrylate polymer blended with polyvinyl chloride resin for water supply (ABR pipe) is modified from PVC pipe, exhibiting high toughness, low temperature, and impact resistance. Experimental and numerical studies were conducted to investigate the mechanical performance of buried ABR pipe by applying traffic load, internal pressure, and a combined traffic load-internal pressure on the buried ABR pipe. The experimental and numerical anlyses were aimed to study the mechanical performance and deformation characteristics of the buried ABR pipe under varying loading conditions. The research results indicated that the mechanical performance of buried ABR pipe was superior, with the most critical sections occurring at 90° and 180°. The circumferential stress of the ABR pipe increased with the growth of internal pressure and traffic load, and the influence of internal pressure was significantly higher than that of traffic load. Additionally, with the increased pipe diameter to thickness ratio, the circumferential stress of the ABR pipe was significantly decreased. Furthermore, a theoretical calculation model for the buried ABR pipe under soil pressure, traffic load, and internal pressure was established based on the prism load method and Moore’s method. Finally, the circumferential stress calculation theory for buried ABR pipe was proposed based on safety factors. This theory was crucial for enhancing the safety and reliability of buried flexible water distribution pipelines under various load conditions.